Mechanisms of Exogenous L-Lysine in Influencing the Quality of Low-Sodium Marinated Braised Beef - Chongxian Zheng; Pengsen Wang; Mingming Huang; Tong Jiang; Jianying Zhao; Yanwei Mao; Huixin Zuo (Foods, 2025)
During the processing of marinated braised beef, excessive sodium intake is likely to occur, which can lead to various health issues. Exogenous L-lysine (L-Lys), as an essential amino acid for the human body, has the capability to enhance the quality of low-sodium meat products. This study aimed to investigate the effects of exogenous L-Lys on the quality of low-sodium plain boiled beef and marinated braised beef, as well as its underlying mechanisms of action. Among them, the substitution rate of KCl was 60%. This study was conducted with three batches of experiments, each batch serving as an independent parallel. For low-sodium plain boiled beef, the optimal addition level of L-Lys was screened out through the research on the effects on meat quality indicators, water distribution, microstructure, and sensory evaluation. For the quality of low-sodium plain boiled beef, in terms of microstructure, the addition of L-Lys reduced muscle fiber breakage and voids, thereby improving its microstructural characteristics. Combined with quantitative descriptive analysis (QDA), the optimal level of additional L-Lys was subsequently determined to be 0.6%. It was further processed into marinated braised beef in soy sauce, and a comparative analysis was conducted with low-sodium marinated braised beef in soy sauce without L-Lys addition for shear force, meat color, thiobarbituric acid reactive substances (TBARS), and total viable count (TVC) during the storage periods of 0, 3, 6, 9, and 12 d. The results show that the redness (a*) value significantly increased within 0–12 d (p < 0.05), leading to a more stable meat color. Moreover, the addition of L-Lys significantly reduced the shear force and thiobarbituric acid reactive species (TBARS) values in the marinated braised beef (p < 0.05), thereby optimizing the tenderness of the marinated braised beef and inhibiting lipid oxidation. Although the total viable count (TVC) of the L-Lys group was higher than that of conventional low-sodium marinated braised beef in soy sauce from 9 to 12 d, both groups of products had undergone spoilage by day 12; therefore, the addition of L-Lys had no effect on the shelf life of the products. Comprehensive analysis suggested that the addition of exogenous L-Lys could optimize beef quality by enhancing hydration, improving muscle structural properties, and exerting antioxidant synergistic effects.